Akses Pelayanan Rumah Sakit Menjadi Faktor Dominan Kepatuhan Minum Obat pada Penderita Skizofrenia - Lia Sitawati; Caroline Endah Wuryaningsih; Dien Anshari (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2019)
Background: Schizophrenia is a severe mental disorder. Schizophrenia Aff 21 million people in the world. Household members (ART) in Indonesia who suffer from Schizophrenia / psychosis 6.7 per mile in 2018. Purpose: Know the determinants of adherence to take medication in paranoid Schizophrenia patients in Outpatient Poly Lampung Province Region in 2019. Methods: Quantitative research with cross design sectional. The population is all paranoid schizophrenics who seek treatment at the study site with 192 samples taken using a purposive sampling technique. Data were collected using an interview technique with a questionnaire instrument, then analyzed multivariate with multiple logistic regression tests. Results: There was a significant relationship between income (OR = 4.73), level of education (OR = 19.3), access (OR = 5), perception of family support (OR = 2.2), insight related to disease (OR = 3.5) , perception of disease severity (OR = 2.6), perception of drug side effects (OR = 2.6), perception of the role of the Doctor (OR = 5.7) and the role of the Pharmacist (OR = 2.7). Conclusions: Access to hospital services is a dominant factor in increasing adherence to taking medication in schizophrenics in psychiatric hospitals. Efforts to improve access to sufferers through mental health services in primary care.